Schistosomiasis control program in the state of Minas Gerais in Brazil - Sandra Costa Drummond; Sílvio Roberto Sousa Pereira; Luciana Cristina dos Santos Silva; Carlos Maurício de Figueiredo Antunes; José Roberto Lambertucci (Memorias do Instituto Oswaldo Cruz, 2010)
The Schistosomiasis Control Program (PCE) was implemented in Minas Gerais (MG) in 1984. In 1999, the state started the investigation and control of schistosomiasis in 470 municipalities. The aim of the present paper is to report the evolution of this Program from 1984-2007. The program included a coproscopic survey carried out in the municipalities of known endemic areas using a quantitative method. Positives were treated with praziquantel and given a program of health education. The information for this study was obtained from data collected and stored by the Health State Department. From 2003-2007, 2,643,564 stool examinations resulted in 141,284 positive tests for Schistosoma mansoni (5.3%). In the first evaluation after treatment, a decrease in the number of municipalities with prevalence over 10% was documented. In one village, selected for a more detailed evaluation, the percentage of positive tests decreased from 14.9% in the baseline survey to 5.3% after treatment. A reference centre for patients with severe schistosomiasis was created in Belo Horizonte, MG. Based on our findings, we believe that the implementation of PCE in MG is on the right path and in due time these new initiatives will provide desirable results.